Cosmetic outcomes and wound closure time in paediatric transverse laparotomy: A randomised comparison of mass and layered closure techniques - Ituen MA; Akpanudo EI; Eyo CS; Ekot EA (Ibom Medical Journal)
Background: Optimal abdominal wall closure in children should ideally balance efficiency with long-term cosmetic outcomes. This study compared wound closure time and scar appearance following mass versus layered closure in paediatric transverse laparotomies.